Madness and subversion in Saul Bellow's later novels: a deconstructive perspective - Marrouchi, Ramzi
Saul Bellow remarkably overemphasized that the protagonists in his later novels were intellectuals who were trained in the European liberal education, namely, humanities. He supposed that these protagonists would lead modem American society and predict its future. However, they were ostracized from the intellectual center of modem American scene. They were marginalized and rejected by the ethics of capitalism, and therefore, prevented from any moral or ethical change. This situation aggravated their alienation, and summoned the deconstruction to the norms of mass culture. The researcher addressed this gap in knowledge, the problematical position of intellectuals in their society, and acknowledged that deconstructing the negativity of capitalism helped solve this intellectual and moral decay in America. Researchers, mass society, intellectuals and policy makers benefited from the insights of this research, its results and recommendations. They paid more attention to the silenced voices of intellectuals. This would help them establish better moral standards away from the negativity of capitalism. This dissertation examined the way these intellectuals, as wise heroes in European humanistic tradition, deconstructed the low culture norms of their society. This study used a combination of Derrida's premises on deconstructionism, Foucault's conception of "episteme" and de Man's view on blindness and insight in order to explain the social and historical fracture from which Bellow s intellectuals suffered. It investigated the manifestations of deconstruction in Bellow's later novels, and explained the wa deconstruction made the transition of social values possible. To accomplish these aims, the concepts of madness, subversion, agony, decline of civility and capitalism were extracted, studied, analyzed and finally classified into juxtaposed tables, as according to the concept of deconstructionism. Findings showed that madness was the wisdom of alienated intellectuals, who sought to establish morality and humanism in modem American society. Thus, madness was envisioned in terms of morality and wisdom. It was also discovered that these intellectuals suffered from the decline of civility. This implied their struggle against the illusive ideals of capitalism. More strikingly, it was revealed that they deconstructed the very ethics of capitalism as they represented the core cause of this cultural and humanistic decline. This study was the first that purported to investigate Bellow's later novels from a de constructive perspective. Consequently, it helped demystify the way capitalism replaced modem European humanistic tradition, and produced, thereby, vulgar masses, instead of traditional intellectuals. Additionally, it facilitated the unveiling of the Bellovian paradigm, which was unrealizable in a society where democracy and capitalism were dominant ideologies. This study paved the way for other researchers to address how the intellectuals in European liberal education faded away in history, regardless of the painstaking efforts made by a small group of elites, including Bellow. Also, it contributed to the previous studies by analyzing Bellow's later novels in line with the poststructuralist theory, namely deconstructionism.